The Influence of Live Music Quality and Menu Pricing on the Consumer Attraction of Generation Z at Kulumanu Kopi Café in Tangerang City - Sosrowidigdo, Suryanto (Jurnal Multidisiplin Sahombu, 2025)
This study investigates the influence of live music quality and menu pricing on the consumer attraction of Generation Z at Kulumanu Kopi Café in Tangerang City. The research adopts a quantitative approach, utilizing a structured questionnaire distributed to respondents who represent Generation Z consumers. The findings reveal that both live music quality and menu pricing significantly affect consumer attraction, with menu pricing showing the more dominant influence. Generation Z consumers tend to value not only affordability but also the overall experience offered by a café, including entertainment elements such as live music. This study highlights the importance of combining pricing strategies with experiential features to attract and retain young customers. The results are relevant for café owners and marketing practitioners seeking to develop competitive strategies tailored to the preferences of the younger generation. Further research is encouraged to include additional factors such as service quality, ambience, or digital engagement.